Elpis Kesaratsian and the Journal “Guitar” - Hambardzumyan, Naira (Bulletin of Yerevan University B: Philology, 2025)
This article focuses on Elpis Kesaratsian (1830-1913), the first Armenian female editor who founded and published the “Guitar” magazine (1861-63) but has been neglected in the field of Armenian history and culture studies for more than 162 years. This study sheds light on the geopolitical and historical contexts in Constantinople in the second half of the 19th century, the imperial censorship, the criticism with regard to the magazine “Guitar”, the unbreakable will that the first Armenian female editor, who also acted as writer, publicist, journalist, translator, Elpis Kesaratsian was guided by throughout her life as a representative of a Christian national minority living in the 19th century Ottoman Empire. The many roles of Elpis Kesaratsian, including those of woman-editor, woman-publicist, woman-publisher, woman-book author, woman-translator, woman-lead nurse, woman-teacher that she fulfilled under the oppression and censorship of the Ottoman Empire, were revealed through investigative, biographical and comparative analyses. Our findings revealed that Elpis Kesaratsian’s main goal was the improvement of the society.